2014
DOI: 10.2135/cropsci2013.10.0707
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Regulator and Soil Surfactants’ Effects on Saline and Deficit Irrigated Warm‐Season Grasses: I. Turf Quality and Soil Moisture

Abstract: A study was conducted at New Mexico State University in Las Cruces, NM, from 2010 to 2012 to investigate the effects of deficit irrigation on bermudagrass (Cynodon dactylon L.) cultivar Princess 77 and seashore paspalum (Paspalum vaginatum Swartz) cultivar Sea Spray treated with either soil surfactants [Revolution (modified methyl capped block copolymer) or Dispatch (alkyl polyglucoside blended with a straight block copolymer)] or a plant growth regulator [Trinexapac‐ethyl (TE); 4‐(cyclopropylhydroxymethylene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 30 publications
11
50
1
Order By: Relevance
“…Moreover, our visual quality data mirrored percentage green cover and NDVI measurements and our correlation analysis indicated a strong association between quality and NDVI and cover. These findings support those of Schiavon et al (2014) and Leinauer et al (2014) who also reported a significant correlation between subjective quality ratings taken on an ordinal scale and objective NDVI and DIA measurements.…”
Section: Soil Hydrophobicitysupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, our visual quality data mirrored percentage green cover and NDVI measurements and our correlation analysis indicated a strong association between quality and NDVI and cover. These findings support those of Schiavon et al (2014) and Leinauer et al (2014) who also reported a significant correlation between subjective quality ratings taken on an ordinal scale and objective NDVI and DIA measurements.…”
Section: Soil Hydrophobicitysupporting
confidence: 89%
“…Schiavon et al (2014) also demonstrated increased soil moisture uniformity and greater turf quality of bermudagrass treated with a liquid surfactant. Our study indicates that a higher VWC uniformity may be a better predictor of turfgrass quality than an average VWC.…”
Section: Soil Hydrophobicitymentioning
confidence: 86%
“…Detailed information on soil properties, irrigation water salinity and sodicity, irrigation system uniformity and irrigation amounts for these research reports are listed in Table 2. The range of values reported in these studies underscores how numerous factors, such as climate and irrigation (precipitation, leaching fraction), soil type and original soil salinity, salinity of irrigation water, and system distribution uniformity, all influence and contribute to changes in soil salinity following irrigation with saline water (Devitt et al, 2007;Ganjegunte et al, 2013;Qian and Mecham, 2005;Schiavon et al, 2014;Sevostianova et al, 2011aSevostianova et al, , 2011bThomas et al, 2006). Developing appropriate salinity management and remediation strategies requires detailed information on the distribution of salinity (EC e ) within the turf root zone.…”
Section: Soil Salinity Of An Urban Park After Long-termmentioning
confidence: 91%
“…Water sample analyses indicated that irrigation water although saline (C3-S1 as per Richards, 1954) was of relatively better quality (lower salinity and sodicity) than the salinity values reported for other ground waters in the area used for irrigation (Schiavon et al, 2014;Sevostianova et al, 2011aSevostianova et al, , 2011b. The Chamizal Memorial is located on the Rio Grande river flood plain and ground water is derived from freshwater zone of the Rio Grande Aquifer.…”
Section: Irrigation Water Quality Apparent Electrical Conductivity Dmentioning
confidence: 95%
See 1 more Smart Citation